Multiproxy geochemical characterization of Kommugudem Formation, Krishna Godavari Basin, India: Implication on hydrocarbon potential and shale brittleness. Issue 4 (8th December 2021) - Kala, Shubhangi; Devaraju, Javaregowda; De, Sanjukta; Rasheed, Mohammed Abdul
Abstract : The unconventional reserves are vital future energy resources and globally augmented interest endeavours the discovery of gas and oil‐rich shales. The Kommugudem Formation, Krishna Godavari Basin was evaluated based on sample laboratory and well log studies from six wells deciphering mineralogical and organic geochemical parameters to provide an understanding of hydrocarbon potential and brittleness. Kommugudem Formation constitutes Type III kerogen dominantly with high total organic carbon (TOC) and T max indicating the presence of high organic matter. The mean vitrinite reflectance indicates mature to post‐mature shale majorly in the gas generation window. Fourier transform infrared spectroscopy functional group investigation revealed the presence of aromatics and aliphatics with a higher degree of abundance owing to higher TOC content. The basic well logs recorded in the studied region are used to estimate the continuous TOC and porosity of the formation and corroborate with laboratory core data. Petrographic, X‐ray diffraction, and field emission scanning electron microscopy studies revealed the presence of dominantly siliceous mineral matter with relatively lower clay and carbonates. Organic mudstone classification indicates formation is dominantly silica‐dominated lithotype and clay‐rich siliceous mudstone. Microfractures and micropores are observed in mineral and organic matter that may act as storage sites for hydrocarbons. Kommugudem Formation on the basis of mineralogy indicates compositional analogy with brittle zones of Barnett Shale Formation. The high mineralogical brittleness index of the Kommugudem Formation indicates good conditions for hydraulic fracturing. The present investigation demonstrates excellent hydrocarbon generation potential and good brittleness in wells A and B while C, D, E, and F have relatively lower potential and may have low gas and oil sources.